Integrated Soil Nutrient Management Technologies for Improved Maize (Zea Mays L.) Productivity in Murang’a and Tharaka-Nithi Counties, Kenya - Otieno, Erick Oduor (University of Embu, 2018)
Continuous land cultivation without adequate soil nutrients replenishment causes soil fertility decline leading to reduced crop productivity. Significant research on external fertility inputs application rates and type have been carried out under researcher designed and managed conditions in Kenya. But little research on the same has been carried out to evaluate their performances under on-farm smallholder farmers’ conditions. Hence, the study evaluated the decomposition rates (goat manure and Tithonia diversifolia) and performance of selected integrated soil nutrients management technologies on soil nutrients amounts and maize productivity under two tillage methods. On-farm trials were laid out in randomized incomplete block design. There were two control treatments; conventional tillage-control (CON-C) and minimum tillage-control (MIN-C). Each tillage method was combined with different soil fertility inputs. Soil fertility inputs included mineral fertilizer, rock phosphate, crop residue, legume intercrop, goat manure and Tithonia diversifolia. Compared to CON-C, in Meru South, N and K significantly increased under minimum tillage+crop residue+Tithonia diversifolia+goat manure and minimum tillage+crop residue+Tithonia diversifolia+rock phosphate by 100 and 52%, respectively. In Gatanga, nitrogen, phosphorus and potasium significantly increased under minimum tillage+mineral fertilizer, conventional tillage+crop residue+mineral fertilizer+goat manure and minimum tillage+crop residue+goat manure+legume intercrop by 33, 78 and 34%, respectively. The highest decomposition rate constants were 0.024 and 0.015 d-1, and 0.020 and 0.014 d-1 for Tithonia diversifolia and goat manure in Meru South and Gatanga, respectively. Relative to CON-C, minimum tillage+crop residue+Tithonia diversifolia+rock significantly increased maize grain yield by 89 and 91% in Meru South and Gatanga during SR2016 and LR2016, respectively. The selected soil nutrient management technologies were preferred based on the ability to improve soil fertility, crop yield, ease of implementation, availability of inputs and labour and farmer’s age. The study concludes that selected soil nutrients technologies improve soil fertility and maize grain and stover yields thus are likely to be taken up by farmers. Tithonia diversifolia and goat manure can be used to synchronize crop-nutrient release.